Amlodipine improves symmetric dimethylarginine in dogs with chronic kidney disease - Morita, Shohei; Mochizuki, Youhei; Kondo, Takahiro; Matsuda, Yasuyoshi; Ohmori, Takahiro; Yoshimura, Aritada; Fukushima, Ryuji (Frontiers in Veterinary Science, 2025)
IntroductionIn canines, chronic kidney disease (CKD) is frequently associated with high blood pressure. Amlodipine is used to treat hypertension in dogs, and we anticipated that amlodipine administration might improve renal function in dogs. However, the effect of amlodipine on canine renal function is unknown. Therefore, this study evaluated changes in symmetric dimethylarginine (SDMA) levels before and after amlodipine administration in pet dogs that had been diagnosed with CKD based on persistently elevated SDMA levels and were being treated with amlodipine alone for any reason. We also conducted a comparative investigation of whether there were any differences in SDMA changes depending on whether these dogs with CKD had hypertension.MethodsThis study employed a retrospective design. The study subjects were pet dogs that exhibited persistently elevated SDMA (≥14 μg/dL), were diagnosed with CKD, and were treated with amlodipine. Profile data such as breed, sex, and age, as well as data on blood chemistry tests, blood pressure, heart rate, and echocardiograms before and after amlodipine administration, were collected. Forty-five dogs were included in the study, of which 20 were hypertensive (HT: systolic arterial pressure ≥160 mmHg) and 25 were non-hypertensive (Non-HT: systolic arterial pressure <160 mmHg).ResultsMean SDMA was significantly lower after drug administration compared with before administration in both the HT and Non-HT groups. Moreover, we found that cardiac output (CO) increased in all dogs with CKD treated with amlodipine. Blood pressure measurements showed that the blood pressure decreased in both the HT and Non-HT groups.DiscussionIt is believed that the increase in CO due to amlodipine administration increases glomerular filtration rate, which may have led to a decrease in SDMA levels. Based on the rate of decrease in systolic arterial pressure, we considered that amlodipine might decrease blood pressure by a greater amount in patients with higher levels of hypertension. In this study, we showed that amlodipine administration improved SDMA in dogs with CKD regardless of whether they were hypertension. We also showed that amlodipine could be safely used to treat normotensive dogs.